Sakai: A Mobile Learning Platform - Abdul Talib, Corrienna; Aliyu, Hassan; Abdul Malik, Adi Maimun; Hooi Siang, Kang; Novopashenny, Igor; Ali, Marlina (International Journal of Interactive Mobile Technologies (iJIM), 2019)
These days, humans have been witnessing related technological and social development, by means of which mobile technologies and Internet yield global access to information with mobility of knowledge. Mobile learning platforms are designed based on electronic learning (e-learning) and mobility. It is regarded as a useful way to enhance the learning process. Sakai as a mobile learning platform, design intentions are to be adaptable to any educational purposes, within or outside the institution, dependent on the provision of effectiveness in classroom instruction based on the learning style of the students, extensible in the cultivation of thinking skills in the learner, and efficient in communicating and exchanging data among its enrolled classroom members and other online platforms. This study employed a systematic review of related literature to investigate the predominant research methodology adopted by various scholars to assess necessary factors concerning mobile learning platform. Fifteen articles are selected based on established criteria. The findings indicated that most of the researchers used quantitative research methodology in investigating the effectiveness and concern variable of mobile learning. Also find out is that most of the outcome of the studies include, achievement, perception, pedagogy, motivation and mobile learning platform as a form of educational technology.